Pendekatan Interkoneksi Dalam Pengajaran Bahasa dan Nilai Islam - Nurjannah, Siti; Fatonah, Siti (LP2M Universitas Islam Ahmad Dahlan, 2024)
Language plays an important role in communication and learning, as well as serving as a means to instil moral and spiritual values. However, language teaching and the application of Islamic values are often conducted separately, which results in a limited impact on the overall development of students. This study aims to analyse the concept of the interconnection approach in language teaching and Islamic values, as well as examine its impact on education in Islamic-based institutions. This research employs a qualitative descriptive method with a literature study approach, analysing various relevant sources to find the relationship between language teaching and Islamic values, as well as its effect on the formation of students' Islamic character. The results show that the interconnection approach can integrate linguistic competence with the reinforcement of Islamic values, creating a learning experience that not only improves language skills but also internalizes moral and spiritual values. This approach, by combining linguistic and religious aspects, provides an innovative solution to face the challenges of globalization in education. The interconnection approach is expected to be an effective learning model, equipping students with solid language skills while making Islamic values a moral guide in daily life.